Kinetics of biogas production in Anaerobic Filters. (January 2016) - Krümpel, Johannes; Schäufele, Friedrich; Schneider, Johannes; Jungbluth, Thomas; Zielonka, Simon; Lemmer, Andreas
Highlights: High precision online measurement. Baseload operation with VFA injections into an Anaerobic Filter. New method determining kinetic parameters & gas yield simultaneously. kinetic parameters show significant differences between acetic propionic and butyric acid. Abstract: This study investigates methane production kinetics from individual volatile fatty acids (VFA) in an Upflow Anaerobic Filter (AF). 1 g COD in the form of acetic (HAc), propionic (HPr) or butyric acid (HBu) was injected into the AF while operating at an organic loading rate (OLRCOD ) of 3.5 g L - 1 d - 1 . A new method is introduced to separate gas production of the baseload from the product formation of VFA degradation after the injection. The lag phase, fractional rate of gas production and half-life has been determined for the methane production of the three VFAs. The half-lives were in the order HAc < HBu < HPr showing a slower gas production from the C3 acid than from the C4 acid. The results can be used for prediction models for on-demand biogas production, a vital approach that provides the transforming energy market with balancing power.